EXPERIMENTAL CONVERSION FELLINGS IN PINE STANDS OF EAST POLISSYA - Zhezhkun, A. M. (Forestry and Forest Melioration, 2018)
Introduction The actions on forests quality improvement and the resilience and productivity restoration include conversion and forest hygienic felling. According to the “Regulations on the improvement of qualitative composition of forests” (2007), conversion and forest hygienic felling includes combined felling along with traditional types of felling. The complex felling combines elements of principal felling and cleaning cutting. The combined felling is subdivided into regeneration felling and conversion felling. Conversion felling is held to convert the even-aged uniform-species forests to uneven-aged mixed stands, basing on the principles of sustainable forest management with the conservation of biodiversity, taking into account environmental, social and economic requirements. In lowland forests of Ukraine, the conversion felling is held only for research purposes. In forests of East Polissya the conversion felling has not previously been conducted. The aim of the research is the implementation of experimental conversion felling for the determination of optimal parameters of organizational and technical elements of cutting in the pine stands of East Polissya. Materials and methods Pine stands of East Polissya are mostly of artificial origin (234.7 thousand hectares or 80.9 % of the area of pine forests). In State Enterprise “Novgorod-Siverska forest research station”, in middle-aged pine stands of artificial origin, the research conversion felling was implemented from 2009 to 2013 on a total area of around 37 hectares. For the gradual transformation of even-aged uniform-species forests into uneven-aged mixed composition the following variants were tested: 1) The formation of square gaps with a side length of 1.5 to 2.0 of average height of the stand (the lengths ratio is 1 : 1); 2) The formation of rectangular gaps with the short direction of about 1.0 of height, and the long one of 1.5 of average height of the stand (the lengths ratio is 1 : 1,5); 3) The formation of narrow cutting areas (narrow strips having width of 1.0-1.5 of average height of the stand) running along the whole area (200–400 m) (the length ratio is 1 : 4 and more); 4) The formation of round-shaped gaps with a diameter ranged from 1.0 to 1.5 of average height of the stand; 5) The formation of round-shaped gaps with a diameter ranged from 1.0 to 1.5 of average height of the stand and uniform thinning out in regeneration strip that is neighboring to the gap; 6) Uniform thinning out of the stand. In the 1, 2, 4, 5 variants of the experiment, the area of each of the gaps was 0.10–0.25 ha. In option 3, the area of the gaps was ranged from 0.9 to 1.1 ha. Permanent plots were laid by standard methods to determine the intensity of felling and the tree mortality after the cuttings. The sanitary condition category of the trees was determined by the “Sanitary rules in forests of Ukraine” (1995). The results and conclusions. The conversion felling research is carried out to convert even-aged uniform-pine stands to uneven-aged mixed pine stands. Scots pine stands with a stand density of 0.6 or more in the presence of dead trees of Kraft classes I–II or weakened trees of more than 20 % their total number are the subject to conversion felling. In different variants of study, the intensity of the first conversion felling was about 25 % of the stock volume of forest stands. Merchantability of timber harvested in the first conversion felling was as follows: timber – 53–74 %, industrial feedstock – 15–21 %, fuel wood – from 11 to 26 %. Tree removal by narrow strips of 1.0–1.5 of the stand height as well as by ringed spaces of 1.5 of the stand height, with a thinning out of stand in neighboring regeneration strip, showed the highest values of dead wood in left parts of the forest. Therefore, the most appropriate is the creation of rounded gaps with a cross-section size of 1.0 of average stand height. After first conversion felling, resistance of a pine forest is provided in the plots with the rectangular or square gaps with a diameter from 1.0 to 1.5 of average stand height (an area is not more than 600 m2). The number of regeneration gaps should be no more than 5 per 1 ha. In even-aged pine stands, the gradual method of conversion felling is applied. The removal of trees in winter just before the Scots pine seeds falling, at cone crop of 3 points or higher, ensures satisfactory pine regeneration. For this reason, either autumn or winter season should be chosen for conversion felling. After the conversion felling during the growing season (after seeds falling) it is necessary to implement measures to promote pine regeneration (loosening the soil, sowing seeds, planting seedlings of trees of principal species). Every next conversion felling is assigned after canopy closing of young stands of principal tree species in previously felled areas, with simultaneous tending felling in the young generation.